Analysis of the Implementation of Regulations and Enforcement of Business Competition Law : Comparative Study of Indonesia, Malaysia, and Thailand - Fauzi, Muhammad Fauzi Rais (Law Research Review Quarterly, 2025)
This research seeks to address several key research questions, namely how the implementation and enforcement of competition law in Indonesia compares with those in Malaysia and Thailand. The focus of the study includes identifying significant similarities and differences between the three countries in terms of regulations, policy implementation, and the effectiveness of their law enforcement agencies. Through a comparative analysis approach, this study is expected to provide a deeper understanding of the effectiveness of competition law implementation and its impact on creating a healthy, fair, and competitive business climate in Southeast Asia. The results show that substantially all three countries, namely Indonesia, Malaysia, and Thailand, share a similar basic regulatory framework, particularly regarding the prohibition of anticompetitive agreements and abuse of dominant position. However, there are important differences in terms of implementation and enforcement. Indonesia relies on the Business Competition Supervisory Commission (KPPU), Malaysia has the Malaysia Competition Commission (MyCC), and Thailand has the Office of Trade Competition Commission (OTCC). Each of these institutions has distinct characteristics and working mechanisms, reflecting the social, economic, and political conditions in their respective countries, thus influencing the effectiveness of competition law implementation in the region.